Persepsi Mahasiswa terhadap Penggunaan Platform Readlang Berbasis Web untuk Pembelajaran Kosakata pada Mahasiswa Pendidikan Bahasa Inggris Semester Pertama di Universitas Muria Kudus - Ahmad Abdul Ghofar Al Zidan; IKA WIDYA ANGGITA; Muhammad Taufik Ali Mustofa; Alyatul Mardiah; Nuraeningsih (Universitas Muria Kudus, 2026)
This study investigated students’ perceptions of the use of the web-based Readlang platform for vocabulary learning among first-semester English Education students at Universitas Muria Kudus. A descriptive quantitative research design was employed using a close-ended questionnaire consisting of 20 items based on four indicators: perceived usefulness, perceived ease of use, engagement, and vocabulary learning support. The participants were 33 students selected through purposive sampling, and the data were analyzed using descriptive statistical techniques, including mean and percentage scores. The findings revealed that students generally had positive perceptions toward the use of Readlang for vocabulary learning, with all indicators falling within positive perception categories. Engagement and vocabulary learning support obtained the highest scores, while perceived usefulness showed the lowest score but remained within a positive category. Overall, the results suggest that Readlang is perceived as an engaging, easy-to-use, and supportive platform for vocabulary learning and has the potential to be integrated into vocabulary learning activities in higher education contexts.